Profissionais liberais e/ou professores? Compreendendo caminhos, representações e avaliação da docência na educação superior - Volpato, Gildo (Universidade do Vale do Rio do Sinos, 2007)
This work is the result of a research on university teaching carried out in three universities in the state of Santa Catarina, Brazil, focusing on the programs of Law, Civil Engineering and Medicine. Some professionals, in spite of their lack of a specific graduation on teaching, after some years of academic experience, become a reference to their students, as the institutional evaluation statistics indicate. Based on that, I decided to investigate and understand the representations and pedagogical practices performed by those professionals positively evaluated by the students. Possible interfering facts and impacts connected to the personal history of the professors, the institutional evaluation systems, the professional field, and the general social context were considered. The approach used was predominantly qualitative and ethnographic and the procedures adopted were: documental analysis, questionnaires and interviews with focal groups of students of the three institutions. Semi-structured interviews wer
Keywords: avaliação institucional; docência universitária; inovação pedagógica; práticas pedagógicas; saberes docentes; profissionais liberais; institutional evaluation; pedagogical innovation; pedagogical practices; teaching knowledge; university teaching; liberal professionals; Ciências Humanas